Iodine‐Mediated Synthesis of Methylthio‐Substituted Catechols from Cyclohexanones - Wu, Yue‐Hua; Wang, Nai‐Xing; Zhang, Tong; Yan, Zhan; Xu, Bao‐Cai; Inoa, Joan; Xing, Yalan (Advanced synthesis & catalysis, 2019)
A novel and efficient I2‐mediated direct synthesis of methylthio‐substituted catechols from cyclohexanones was developed. Various cyclohexanones underwent oxygenation, methylthiolation, and dehydrogenative aromatization in one pot to form the desired products in moderate to good yields. DMSO was utilized as the solvent, oxygen source, and methylthiolation agent. A possible reaction mechanism is proposed.